Efficiency Optimization Method of Parallel DC/DC Converter Based on Sequential Quadratic Programming - Xie, Tian; Huang, Jingjing; Zhao, Limin; Wang, Shuo (IEEE International Conference on Power and Energy Applications (Online), 2024)
Interleaved parallel bidirectional DC/DC converters are widely used in various application fields due to their high power density and scalability. However, variations in the internal resistance of each module can lead to power switching losses and uneven load current distribution. Consequently, some modules with higher efficiency may operate at non-optimal points, which diminishes the overall system efficiency. Therefore, identifying an optimal load current distribution scheme is crucial. By optimizing the current distribution, each module can operate near its optimal power output point, maximizing overall system efficiency and minimizing energy waste. This paper proposes an efficiency optimization strategy based on the sequential quadratic programming method. By establishing an efficiency model for the parallel DC/DC converter system, we utilize this method to determine the optimal load current distribution. This approach enhances the overall operational efficiency of the system. Simulation results indicate that, compared to traditional current sharing control strategies, the overall system efficiency is improved by up to 1.01%, significantly enhancing energy utilization.